ALIVE : Advancements in adaptive architecture. - Kretzer, Manuel (Applied virtuality book series., 2014)
In times where the very concept of 'nature' is questioned not only in its philosophical dimension, but in the core of its biological materiality, we need to reconsider the interrelations between architecture and nature. To address these challenges this book unravels compelling innovative and forward-thinking design narratives by leading international practitioners and researchers for a future, alive architecture.